Malaya-nigeria political parties ideologies in comparative study 1945 to independence - Haruna, Nasiru; Md Nor, Mohd Sabri; Mohd Nor, Murni Wan; Ismail, Mohd Mahadee (Human Resource Management Academic Research Society, 2023)
The analogy of Malaya and Nigerian politics was invented by British colonial masters that rule in both countries during the colonial era. However, in Malaya and Nigeria, issues ethnicity, religion and races played a dominant role in political parties’ formation. Therefore, this paper will identify and compare the ideologies of United Malay National Organization (UMNO), Northern People Congress (NPC), National Council of Nigeria and Cameroon (NCNC) and Action Group (AG), in their struggle to obtain the independence. Secondary data were use and critically analyzed with the view to came out with the reliable information. Similarities of the both parties in Malaya and Nigeria engaged in organized public opinion between the colonial government and the citizens, served as a pressure group. UMNO as political party has the national outlook express the views of all the Malay in Malaya while the Nigerian political parties lack national outlook each party fight for the independence of its autonomous Region and ethnic group, which delay the independence of the country to 1960 and Malaya in 1957. To strengthen the long-standing relationship of Malaya and Nigeria and to expose the past polities to the present generation in order to determent the future of their country’s politics.